Polski system edukacyjny w obliczu utopijnej wizji integracji osób niepełnosprawnych - Jerzyk, Marta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In many developed European countries, the integration of people with disabilities into full life in society takes place primarily on the basis of integral education. Currently one of the priorities of the Polish education system is the integration of pupils with various disabilities with their able peers in mass institutions or in integration departments. The aim of this thesis is to try to systematize the basic knowledge about integration education for children and young people with disabilities, to show the main directions of its transformation, and to build an expanded reality related to the education of people with disabilities. Despite many social, economic and legislative changes, during permanent development of the state, Polish educational system in many aspects is unable to realize today’s utopian vision of integration education.
Keywords: disability; education; integration